Non-Linguistic Analysis of Call Center Conversations - Kopparapu, Sunil Kumar; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
The book focuses on the part of the audio conversation not related to language such as speaking rate (in terms of number of syllables per unit time) and emotion centric features. This text examines using non-linguistics features to infer information from phone calls to call centers. The author analyzes "how" the conversation happens and not "what" the conversation is about by audio signal processing and analysis.
Overview -- Voice Analytics Process -- Call Center Linguistic Analytics -- Non-linguistic Speech Processing -- Case Study.-Conclusions.
Keywords: Engineering; Computational linguistics; Linguistics; Engineering; Signal, Image and Speech Processing; Language Translation and Linguistics; Linguistics, general; Electronic books